Polymer Solar Cells: Panchromatic Sequentially Cast Ternary Polymer Solar Cells (Adv. Mater. 4/2017). Issue 4 (January 2017) - Ghasemi, Masoud; Ye, Long; Zhang, Qianqian; Yan, Liang; Kim, Joo‐Hyun; Awartani, Omar; You, Wei; Gadisa, Abay; Ade, Harald
Abstract : To increase the range of light absorption in polymer solar cells, two absorber donor polymers (blue and red, respectively) are utilized. In article 1604603, H. Ade and co‐workers mix these polymers separately with a fullerene acceptor (grey) and process them using a new deposition strategy to create sequentially cast ternary (SeCaT) polymer solar cells that exhibit a bilayer structure without an interlayer.